KEHUJAHAN MAQASID AL-SYARI’AH - Dr. Andi Muhammad Akmal (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2018)
The study of maqasid al-syariah is very urgent in the effort of legal ijtihad. That is, because it becomes the basis of law enforcement. The purpose of the law must be known by every mujtahid to answer the problem that the law is not clearly regulated in the Qur'an and Sunna and in order to develop the thinking and reform of Islamic law. Orientation of the realization of the goal of sharia or maqasid al sharia, namely the public interest. Public interest which is the core and purpose of sharia should be guided by the basic principles and values ​​of the Qur'an and Sunna.Upaya excavation syara 'law, will be successful and optimal, if understand maqasid al shariah well.